2022
DOI: 10.1007/s00127-022-02382-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the early phase of the COVID-19 pandemic on the use of mental health services in South Korea: a nationwide, health insurance data-based study

Abstract: Purpose The coronavirus disease 2019 (COVID-19) pandemic has profoundly affected the utilization of mental health services. Existing evidence investigating this issue at the nationwide level is lacking, and it is uncertain whether the effects of the COVID-19 pandemic on the use of psychiatric services differs based on psychiatric diagnosis. Methods Data from the claims database between October 2015 and August 2020 was obtained from the Health Insurance Review and Assessment agency in South Korea. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Psychiatric inpatient admissions that decreased during the first shutdown also recovered quickly after the relief of the measures, similar to observations from Canada [15] and Italy [40] and faster than in South Africa [17] and South Korea [18]. Importantly, the decrease in psychiatric inpatient admissions during the first shutdown was comparable to that of general emergency inpatient procedures but considerably smaller than that of general elective inpatient procedures in Switzerland [36].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Psychiatric inpatient admissions that decreased during the first shutdown also recovered quickly after the relief of the measures, similar to observations from Canada [15] and Italy [40] and faster than in South Africa [17] and South Korea [18]. Importantly, the decrease in psychiatric inpatient admissions during the first shutdown was comparable to that of general emergency inpatient procedures but considerably smaller than that of general elective inpatient procedures in Switzerland [36].…”
Section: Discussionsupporting
confidence: 73%
“…At the same time, the pandemic has affected the provision of mental healthcare, particularly in the beginning of the pandemic and in periods with many COVID-19 cases when healthcare services had to be reorganized in order to reduce the spread of the virus and to ensure care capacities for people with COVID-19. Accordingly, decreases in different forms of mental healthcare utilization, especially during shutdown periods, have been reported, e.g., in hospitalizations and/or emergency department visits for mental health diagnoses [15][16][17][18], presentations for or diagnoses of mental health conditions in primary care [19,20], and general population antidepressant drug purchase [21]. However, some studies also reported increases for certain mental healthcare utilization outcomes as the pandemic progressed, e.g., increases in antidepressants fillings in the general population [22] or in mental health outpatient visits especially among children and adolescents in the summer of 2020 [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…Data on ED and hospital admissions for psychiatric disorders during the pandemic remain inconsistent with the majority of studies conducted internationally. For example, the studies from Europe, UK, Australia, South Korea and Canada variably reported both increases or decreases in visits [7][8][9][10][11][12][13][14][15][16][17][18]. In the United States, there were inconsistent and limited data on ED visits and admissions for adults in Midwest, rural areas of West Texas, urban Kentucky and New York City as well [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%